Constitutive histamine H2 receptor activity regulates serotonin release in the substantia nigra. - Threlfell, S; Exley, R; Cragg, S; Greenfield, S (2008)
The substantia nigra pars reticulata (SNr) forms a principal output from the basal ganglia. It also receives significant histamine (HA) input from the tuberomammillary nucleus whose functions in SNr remain poorly understood. One identified role is the regulation of serotonin (5-HT) neurotransmission via the HA-H(3) receptor. Here we have explored regulation by another HA receptor expressed in SNr, the H(2)-receptor (H(2)R), by monitoring electrically evoked 5-HT release with fast-scan cyclic voltammetry at carbon-fiber microelectrodes in SNr in rat brain slices. Selective H(2)R antagonists (inverse agonists) ranitidine and tiotidine enhanced 5-HT release while the agonist amthamine suppressed release. The 'neutral' competitive antagonist burimamide alone was without effect but prevented ranitidine actions indicating that inverse agonist effects result from constitutive H(2)R activity independent of HA tone. H(2)R control of 5-HT release was most apparent (from inverse agonist effects) at lower frequencies of depolarization (< or = 20 Hz), and prevailed in the presence of antagonists of GABA, glutamate or H(3)-HA receptors. These data reveal that H(2)Rs in SNr are constitutively active and inhibit 5-HT release through H(2)Rs on 5-HT axons. These data may have therapeutic implications for Parkinson's disease, when SNr HA levels increase, and for neuropsychiatric disorders in which 5-HT is pivotal.